Identification of two novel compound heterozygous mutations of ADGRV1 in a Chinese family with Usher syndrome type IIC. (4th July 2018) - Zhang, Nian; Wang, Juan; Liu, Shuting; Liu, Mugen; Jiang, Fagang
ABSTRACT: Background: To describe the clinical and genetic findings in a Chinese family with three sibs diagnosed with Usher syndrome type IIC. Materials and Methods : Four members received ophthalmic and otologic tests to ascertain the clinical characteristics. According to the clinical phenotype, we focused attention on a total of 658 genes associated with them. We screened the possible pathogenic mutation sites, used Sanger to exclude the false positive and verified whether there were co-segregated among the family members.Results: Typical fundus features found in the proband supported the diagnosis of retinitis pigmentosa (RP). Audiometric test indicated moderate to severe sensorineural hearing impairment while the vestibular function was normal. Whole-exome sequencing identified the presence of two novel compound heterozygous mutations in ADGRV1, a known gene responsible for Usher syndrome type IIC. Mutationc.15008delG/p.Gly5003AlafsTer13 was inherited from the mother while c.18383_18386dupACAG/p.His6130GlnfsTer84 was inherited from the father, and they were co-segregated with the disease phenotype in the family.Conclusions: The mutations found in our study not only broaden the mutation spectrum of ADGRV1, but also provide assistances for future genetic diagnosis and treatment for Usher syndrome patients.